An updated review on the principles of intraoperative neurophysiological monitoring and the anaesthetic considerations. Issue 12 (December 2022) - Sanders, Brett; Catania, Santiago; Luoma, Astri MV.
Abstract: It is known that any surgery to the nervous system poses risks to neural structures and their surrounding structures. These mechanisms of injury are the result of mechanical manipulations, haemodynamic alterations, chemical or thermal injuries. Intraoperative neurophysiological monitoring (IONM), using various modalities, is employed to facilitate the assessment of the functional integrity of neural structures, and it is used to provide a real-time alerting system when changes caused by surgically induced insults are detected. The primary goal of IONM is reducing the risk of postoperative neurological deficits during these surgical procedures. It is used to provide information that allows the surgeon to correct any surgical interventions that may have compromised these systems and this also in turn provides guidance on what neurological deficits to anticipate postoperatively. Apart from being utilized as an alerting system to avoid catastrophic outcomes, IONM also assists as a guidance system using stimulation techniques to map out eloquent areas within the cortex, allowing identification of specific neuronal structures, particularly when landmarks cannot be easily recognized due to infiltration by pathological lesions. In this article, we focus on updating our previous paper published in 2019 and again, to provide attention to the various neurophysiological modalities that are employed in IONM. We will look at the basic underlying physiological principles and their individual indications for use clinically. We will explain the information that each modality provides. Importantly, and the primary reason for this article, we look at the various anaesthetic agents, their effects on each neurophysiological modality and other anaesthetic considerations such as haemodynamic and temperature effects. We will also recommend the use of an alert checklist for the multidisciplinary team should an intraoperative alert be issued during surgical procedures.